High incidence of sexual dysfunction and timed intercourse was found only in infertile males who with known impairment of sperm quality for a long period: evidence from a hospital-based cross-sectional study - Xiaowei Yu; Songling Zhang; Linjiao Chen; Xiao Yuan Zhang; Qun Wang (BMC, 2022)
Abstract Background Infertile men with higher sexual dysfunction risk and increased psychological burden, were also associated with more inclined to timed intercourse. Decreased semen quality may have adverse effects on male sexual function. However, it is also likely that many of these sequences do not play a direct role, those negative consequences may depend mainly on the later failed attempting pregnancy. Research is limited in this area. Methods This cross-sectional study was based on a group of 509 men who were assessed for couple's infertility at the First Hospital of Jilin University between June 2021 and October 2021. All the men completed a comprehensive questionnaire, and then were divided in two groups. Group A included patients who either never received a routine infertility work-up or done so recently within the last 6 months. Group B included patients who previously received a sperm quality assessment at least 6 months or more prior. Patients were further categorized into three subgroups according to the severity of the decreases in their sperm parameters: severe, mild-moderate, and normozoospermic. Results The prevalence of erectile dysfunction was higher in Group B Mild-Moderate and Group B Severe in comparison to Group A (OR=1.86 [1.07-3.24], P = 0.027; OR=5.312 [2.69-10.49], P < 0.001, respectively). No significant differences were found between Group A and Group B-normozoospermic. Similar results were observed in the prevalence of premature ejaculation between the groups. Timed intercourse was seen in 11.8% (20/170) of men in Group A and 16.2% (19/117) in Group B-normozoospermic. It was more commonly practiced among infertile men in Group B-Mild-Moderate and Group B Severe, as 28.2% (44/156) and 25.7% (17/66) of these couples had attempted to conceive through timed intercourse (P < 0.001). Conclusions Our findings indicate that the severity of sperm quality impairment was negatively associated with sexual dysfunction only in infertile men who with known impairment of sperm quality for a long period. Timed intercourse was more common among these couples. For those individuals had never test their sperm quality, although more than half of these patients showed a decrease in sperm quality, the incidence of sexual dysfunction is relatively low and were comparable to those men examined previously known as normozoospermic.